THE INFLUENCE OF DIGITAL LITERACY AND PERCEPTION OF EASE OF USE ON PURCHASE DECISIONS: ISLAMIC CONSUMPTION ETHICS AS MODERATION - Az-Zuhdiyyah, Hafshah Afifah; Abdullah, Muhammad Ammar; Rusgianto, Sulistya (Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of digital literacy and perceived ease of use on consumer purchasing decisions on e-commerce platforms, with Islamic consumption ethics as a moderating variable. Digital literacy is considered important because it influences consumers' ability to access and evaluate digital information effectively, while perceived ease of use reflects users' comfort in interacting with the platform. In the context of Muslim consumers, consumption ethics such as halal, fairness, and simplicity are also important considerations in decision-making. This study uses a quantitative approach with a survey method through a Likert scale questionnaire 1–5 to Muslim e-commerce users in Indonesia. The sampling technique used is non-probability sampling with a purposive sampling method of Muslim consumers using e-commerce in Indonesia. The collected data were analyzed using PLS-SEM techniques to test the direct and moderating effects. The results of this study indicate that digital literacy and perceived ease of use have a positive and significant effect on purchasing decisions in e-commerce. However, Islamic consumption ethics is not proven to moderate the relationship between digital literacy and purchasing decisions or between perceived ease of use and purchasing decisions. These findings provide implications for e-commerce players to improve the quality of digital services and also provide input for Muslim consumers to be wiser in utilizing the convenience of digital platforms in accordance with the principles of Islamic consumption ethics.